The Palaeoenvironment Of the Central Russian Plain During the End Of the Valdai Glaciation Based on Small Mammal Data From the Late Palaeolithic Site Byki 7 (Seim R. Basin) - Anastasia K. Markova; Andrey Yu. Puzachenko (Geography, Environment, Sustainability)
The analysis of the Late Pleistocene small mammals’ faunas from the three cultural layers of the Late Palaeolithic site Byki 7 (the Seim River basin) consist of a combination of steppe and tundra species. Steppe species definitely prevail and include Ochotona pusilla, Marmota bobac, Spermophilus sp., Spalax microphthalmus, Ellobius talpinus, Lagurus lagurus and Lasiopodomys (Stenocranius) gregalis. Tundra species (collared lemming and Siberian lemming) are only represented by a small amount of remains. The lack of forest dwellers in the Byki 7 small mammal assemblage indicates of the absence of a continuous forest zone on the Central Russian Plain during the end of the Valdai glaciation. The Eurasian geographical distribution of the Rodentia and Lagomorpha species represented in the Byki–7 assemblages, have been reconstructed for the period of deposition of the site. Radiocarbon dates indicate that the multilayer Late Palaeolithic Byki 7 site correlates with the second part of the Valdai Glaciation Maximum cooling (LGM) (22–17 ka BP). Based on the small mammal data the former palaeoenvironmental conditions of the non-analogue periglacial tundra-steppe are reconstructed.